Modified technique of extracorporeal septoplasty in severe septal deviation - Alwan, Muhanned M.; Dakhil, Husam T.; Hussain, Zainab Ali; Khefi, Raed A. (Oral and maxillofacial surgery cases, 2021)
Septal deviation represent a major cause of aesthetic disorders and respiratory obstruction. The traditional septoplasty techniques may often be inadequate to treat severe deviations. This study was designed to evaluate the effectiveness of the modified technique of extracorporeal septoplasty in terms of subjective improvement in validated NOSE score post-operatively and complications in short term (3months). A total of 20 patients with severe septal deviation were evaluated in the Otolaryngology Outpatient Department in Al-Immamain Al-Khadimain Medical City, from March 2017 to February 2018. All were undergoing extracorporeal septoplasty (ECS) and assessed pre and post-operatively clinically and endoscopically and subjective evaluation of the respiratory function was obtained by mean of Nasal Obstruction Symptom Evaluation (NOSE) scale which compared with the results obtained preoperatively and at 1 and 3 months post-intervention. NOSE scores at 1 and 3 months follow-up demonstrated a statistically significant improvement (P < 0.0001) compared to preoperative values. There were no complications recorded. The modified extracorporeal septoplasty technique proved to be functionally effective at 3-month follow-up in cases of severe septal deviation. •Modified Extracorporeal Septoplasty is very effective clinically and statistically for severe septal deviation.•Elevated the surgeon the ability to correct the septum under direct visualization.•ECS have less complications.